Assessing the Reliability of Optimized Residual Feed Intake Measurements in Beef Cattle - Mononen, Jaakko; Kostensalo, Joel; Pesonen, Maiju; Huuskonen, Arto; Manni, Katariina (MDPI AG, 2022)
Residual feed intake (RFI) is the preferred measurement for feed efficiency in beef cattle, but it is laborious to determine. Data from two experiments of growing bulls (test period durations of 56 and 63 days) were used to examine how a reduction in the number of times the animals were weighed and the shortening of the length of the observation period affect the reliability of the RFI determination. We introduce two easily understandable probability measures for assessing reliability. ‘The consistency of the pair-wise ranks’ gives the probability that the rank of any two animals compared remains the same when the amount of data is reduced. ‘The consistency of the thirds’ gives the probabilities that an individual animal will remain in the same, i.e., the lowest, middle, or highest, third of animals. The reliability of the results was not greatly affected when the weighing interval was reduced from one week to four weeks. However, shortening the test period resulted in a marked reduction in the reliability of RFI. If individual feed intake is automatically measured, the workload required for RFI measurements can most effectively be reduced by reducing the number of weighing times but keeping the duration of the test period long enough.
Keywords: bulls; dry matter; feed efficiency; growth; non-parametric method; test duration